Tingkat Kemampuan Teknik Pukulan Forehand Drive Mahasiswa Olahraga Pada Permainan Tenis Meja - Jeki Haryanto; Eri Barlian; Masrun Masrun; Mert Isbilir; Indra Hanafi; Gusril Gusril; Yendrizal Yendrizal (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
Table tennis is a sport that has the characteristics of a fast game and requires good hitting skills. Athletes who can direct the ball correctly are more advantaged in winning the match. The drive stroke is also a stroke that is often used in table tennis matches. This study aims to determine the level of forehand drive stroke technique ability of sports students. The sample in this study was 12 people (age: 19.75 ± 1.69), and the participants were students who were taking basic table tennis courses. Forehand drive stroke ability data were obtained by conducting a forehand drive ability test and then analyzed with descriptive statistics. The results of this study state that the level of forehand drive stroke ability of sports students in general (50%) is in the lower category. From the results of the study, it is necessary to develop a form of forehand drive training so that sports students and all table tennis players can improve their ability to play table tennis.